HUBUNGAN PEMBERIAN SUSU FORMULA DENGAN OBESITAS PADA ANAK USIA 5-6 TAHUN DI PENDIDIKAN ANAK USIA DINI KECAMATAN MANDIRAJA KABUPATEN BANJARNEGARA - Febriana Triastuti; Tri Anasari Akademi Kebidanan YLPP Purwokerto (Jurnal Kebidanan, 2013)
HUBUNGAN PEMBERIAN SUSU FORMULA DENGAN OBESITAS PADA ANAK USIA 5-6 TAHUN DI PENDIDIKAN ANAK USIA DINI KECAMATAN MANDIRAJA KABUPATEN BANJARNEGARA Febriana Triastuti & Tri Anasari Akademi Kebidanan YLPP Purwokerto ABSTRACT Excessive weight gain in infants can make it have a health problem, one of which is obesity. Obesity is a disorder characterized by accumulation of excess body fat tissue. Bottle fed children will be obese by age five or six years. Infant formula can lead to obesity because it has more short chain saturated fatty acids, whereas unsaturated fats only 3%. The purpose of this research to find out the correlation of giving the formula milk and the obesity in the children in age 5-6 year olds at Early Childhood Education School Sub district of Mandiraja. The type of this research was observational by using the approach of case control. Population in this research was all the children of age 5-6 year olds. The sample of each group is 58 children. Procedure of taking sample for the group of case used the total sampling and the group of control used the simple random sampling. Research instrument used the questionnaire and observation. Data analysis used the chi-square. The most of respondent consumed the formula milk 71 respondents (61.2%). Group of case and group of control each of them 58 cases (50%). There was the correlation between the giving of formula milk and the obesity in the children of 5-6 year olds at Early Childhood Education School Sub district of Mandiraja (p value = 0.000 and OR = 4.26). There was the correlation between the giving of formula milk and the obesity in the children of age 5-6 year olds at Early Childhood Education School Sub district of Mandiraja. Every health officer would be better in order to not giving the Baby Formula Milk and/or other baby product that can impede the program of giving Exclusive Breast Milk except for the baby with the medical indication condition, baby does not has mother or mother is isolated from the baby. Keywords : Formula Milk, obesity, children of 5-6 year olds